Perancangan Media Animasi Merintis Penemuan Sejarah Lamuri - Raihan Islamadina; Rizki Ubaidillah (Jurnal Serambi Engineering, 2020)
Lamreh, one of Aceh Besar regency areas, formerly had a kingdom called Lamuri Sultanate Kingdom. This Sultanate is the forerunner to the Sultanate of Aceh Darussalam. So that the history of Lamuri does not disappear, the writer is interested in providing information about the historical discovery of the kingdom of Lamuri in the form of animation. Lamuri's historical animation is designed in the form of 3-dimensional object visualization with easy-to-understand voice dialogue. Animation uses 3 software in the form of Iclone, Sketchup, and Corel pro x6. This animation amounts to 10 scenes with a duration of 5 minutes 45 seconds. Hopefully, this animation can provide information to the public about the forerunner of the history of Lamuri.